Endothelial‐protective effects of a G‐protein‐biased sphingosine‐1 phosphate receptor‐1 agonist, SAR247799, in type‐2 diabetes rats and a randomized placebo‐controlled patient trial. Issue 5 (26th November 2020) - Bergougnan, Luc; Andersen, Grit; Plum‐Mörschel, Leona; Evaristi, Maria Francesca; Poirier, Bruno; Tardat, Agnes; Ermer, Marcel; Herbrand, Theresa; Arrubla, Jorge; Coester, Hans Veit; Sansone, Roberto; Heiss, Christian; et al.
Abstract : Aims: SAR247799 is a G‐protein‐biased sphingosine‐1 phosphate receptor‐1 (S1P1 ) agonist designed to activate endothelial S1P1 and provide endothelial‐protective properties, while limiting S1P1 desensitization and consequent lymphocyte‐count reduction associated with higher doses. The aim was to show whether S1P1 activation can promote endothelial effects in patients and, if so, select SAR247799 doses for further clinical investigation. Methods: Type‐2 diabetes patients, enriched for endothelial dysfunction (flow‐mediated dilation, FMD <7%; n = 54), were randomized, in 2 sequential cohorts, to 28‐day once‐daily treatment with SAR247799 (1 or 5 mg in ascending cohorts), placebo or 50 mg sildenafil (positive control) in a 5:2:2 ratio per cohort. Endothelial function was assessed by brachial artery FMD. Renal function, biomarkers and lymphocytes were measured following 5‐week SAR247799 treatment (3 doses) to Zucker diabetic fatty rats and the data used to select the doses for human testing. Results: The maximum FMD change from baseline vs placebo for all treatments was reached on day 35; mean differences vs placebo were 0.60% (95% confidence interval [CI] −0.34 to 1.53%; P = .203) for 1 mg SAR247799, 1.07% (95% CI 0.13 to 2.01%; P = .026) for 5 mg SAR247799 and 0.88% (95% CI −0.15 to 1.91%; P = .093) for 50 mg sildenafil. Both doses of SAR247799 were well tolerated, did not affect blood pressure, and were associated with minimal‐to‐no lymphocyte reduction and small‐to‐moderate heart rate decrease. Conclusion: These data provide the first human evidence suggesting endothelial‐protective properties of S1P1 activation, with SAR247799 being as effective as the clinical benchmark, sildenafil. Further clinical testing of SAR247799, at sub‐lymphocyte‐reducing doses (≤5 mg), is warranted in vascular diseases associated with endothelial dysfunction.